2011
DOI: 10.1111/j.1479-8298.2011.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Is parental care behavior in Belostoma species an evolutionary cause for their common sexual size dimorphism pattern?

Abstract: Current evidence suggests that sexual size dimorphism (SSD) reflects the male and female adaptation to their different reproductive roles. Belostoma and Lethocerus species, included in Belostomatidae, present different kinds of paternal care. Females of Belostoma Latreille species lay their eggs on the back of males. Males carry, aerate and protect the clutch until hatching, which is critical for offspring survival. Males of Lethocerus Mayr species exhibit some parental care behavior but do not carry the eggs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…in Sullivan & Miller 2007), larger wing size may indicate larger body size. fecundity (Reeve & Fairbairn 1999;Fischer & Fiedler 2000;Iglesias et al 2012). Sexual dimorphism in wing morphology of butterflies and moths appears to be driven largely by natural and sexual selection that affects males and females differently (Allen et al 2011).…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…in Sullivan & Miller 2007), larger wing size may indicate larger body size. fecundity (Reeve & Fairbairn 1999;Fischer & Fiedler 2000;Iglesias et al 2012). Sexual dimorphism in wing morphology of butterflies and moths appears to be driven largely by natural and sexual selection that affects males and females differently (Allen et al 2011).…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…Iglesias et al (2012) found that in B. bifoveolatum, and in other belostomatid species, the males have relatively longer middle and hind legs than females and provide parental care. The morphology of males allows them to maintain effective locomotion even when carrying the egg pads (Iglesias et al 2012). We observed that egg pad size varied among years at Llao Llao, but this result was not associated with variation in male morphology in either wetland.…”
Section: Discussionmentioning
confidence: 92%
“…Iglesias et al. () found that in B. bifoveolatum, and in other belostomatid species, the males have relatively longer middle and hind legs than females and provide parental care. The morphology of males allows them to maintain effective locomotion even when carrying the egg pads (Iglesias et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies show that the trends of SSD depend on individual species (Iglesias et al . ; Thrasher et al . ).…”
Section: Morphological Studiesmentioning
confidence: 99%